Corporate Governance and Audit Report Lag on Financial Sector Companies Listed in IDX 2018-2020 (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: This study aims to determine the effect of corporate governance practices on the length of time for the annual financial statement audit that called Audit Report Lag (ARL).Method: This research used quantitative approach with a multiple linear regression models through ordinary least square and classic assumptions test. Selection of the sample using purposive sampling method, from financial sector company listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020, 250 data were selected as a sample.Findings: It was found that board size, audit committee meeting and audit opinion variable give negative effect on ARL. Besides, Audit committee size give positive effect on Audit Report Lag.Novelty: This study enriched the literature by finding out that “others” sub sector in financial company didn’t have a specific regulation whereas previous research only focus on bank which alreasy have a strict regulation. This research’s implication is expected to give wider insight to company and regulator that can help them publish their financial reports on time.